Distribution of the social cost of Jamaica's structural adjustment 1977-1989 - Witter, Michael (I.L.O.PREALC Port of SpainTT, 1991)
Puts forward the view that in the Jamaica context, it was the structural adjustment policies which intensified social inequalities and widened the gap between earnings and basic needs. Focusses on 4 periods viz. 1962-1974 - from independence to the imposition of the bauxite levy; 1974-1977 - the economic strategy of democratic socialism; 1977-1982 - economic stabilization by the IMF; and 1982-1990 - economic stabilization. Examines the Jamaican labour market under structural adjustment, reviewing changes in the size and composition of the labour force between 1977 and 1989 and examines the changing distribution of employment by industry and occupation.